2006
DOI: 10.3998/ark.5550190.0008.608
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of 1-carbalkoxymethyl-4-hydroxy-1-methylpiperidinium chlorides

Abstract: The synthesis of new 1-carbalkoxymethyl-4-hydroxy-1-methylpiperidinium chlorides derived from 4-hydroxy-1-methylpiperidine and alkyl chloroacetates was described. Salts were characterized by MS, FTIR, 1 H and 13 C NMR spectroscopies. Compounds investigated were tested against Escherichia coli, Staphylococcus aureus, Candida albicans and Aspergillus niger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Both signals originated from the methyl group attached to the nitrogen atom in the axial or equatorial position. Moreover, it was confirmed that the signal present at the larger chemical shift was derived from the trans isomeric form (Figure A) . On the basis of the integration ratio of these bands, it can be concluded that the molar fraction of the trans form ranges from 49 to 70% (Figure B).…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Both signals originated from the methyl group attached to the nitrogen atom in the axial or equatorial position. Moreover, it was confirmed that the signal present at the larger chemical shift was derived from the trans isomeric form (Figure A) . On the basis of the integration ratio of these bands, it can be concluded that the molar fraction of the trans form ranges from 49 to 70% (Figure B).…”
Section: Resultsmentioning
confidence: 61%
“…During the quaternization of 4-hydroxy-1-methylpiperidine, it is possible to obtain two geometrical isomers, since the alkyl substituent can be attached to the nitrogen atom in the cis or trans position relative to the hydroxyl group. This phenomenon has been already described for the homologous series of 1-carbalkoxymethyl-4-hydroxy-1-methylpiperidinium chlorides . Due to their very similar chemical structures as well as analogous physicochemical properties, attempts to separate the isomeric forms of the quaternary precursors using simple laboratory techniques proved to be ineffective.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Physicochemical characteristics of 11 correspond to those described in the literature. 27 Yellow liquid; yield: 6.58 g (91%).…”
Section: Undecanol Chloroacetate (11)mentioning
confidence: 99%